2018
DOI: 10.1021/acs.organomet.8b00476
|View full text |Cite
|
Sign up to set email alerts
|

Nickel-Catalyzed Oxidative Coupling Reaction of Phenyl Benzyl Sulfoxides

Abstract: A novel method to produce disulfoxides diastereoselectively from phenyl benzyl sulfoxides is reported. The Ni(P n Bu 3 ) 2 Cl 2 ]/NIXANTPHOS catalyst system successfully promotes an oxidative coupling reaction of aryl benzylic sulfoxides to disulfoxides. An intermediate aldehyde, produced from the elimination of α-hydroxy sulfoxides, is proposed to generate the key sulfenate anion, enabling the formation of the disulfoxide product. A range of disulfoxides was produced in moderate to high yields (30−83%) and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 77 publications
0
2
0
Order By: Relevance
“…Walsh and co-workers found that NiXantphos gives 25–48% yields with either (PBu 3 ) 2 NiCl 2 , Ni­(cod) 2, or (dppp)­NiCl 2 in an oxidative homocoupling of phenyl benzyl sulfoxides (eq ). Other Ni sources and ligands lead to no yield.…”
Section: Miscellaneousmentioning
confidence: 99%
See 1 more Smart Citation
“…Walsh and co-workers found that NiXantphos gives 25–48% yields with either (PBu 3 ) 2 NiCl 2 , Ni­(cod) 2, or (dppp)­NiCl 2 in an oxidative homocoupling of phenyl benzyl sulfoxides (eq ). Other Ni sources and ligands lead to no yield.…”
Section: Miscellaneousmentioning
confidence: 99%
“…Other Ni sources and ligands lead to no yield. The reaction is optimized using (PBu 3 ) 2 NiCl 2 and NiXantphos to an 82% yield …”
Section: Miscellaneousmentioning
confidence: 99%